TRIPTOLIDE INDUCES CELL DEATH IN PANCREATIC CANCER CELLS BY APOPTOTIC AND AUTOPHAGIC PATHWAYS - Mujumdar, Nameeta (2010)
BACKGROUND & AIMS: Pancreatic adenocarcinoma, among the most lethal human malignancies, is resistant to current chemotherapies. We have previously shown that triptolide inhibits the growth of pancreatic cancer cells in vitro and prevents tumor growth in vivo. This study investigates the mechanism by which triptolide kills pancreatic cancer cells, which has not been previously studied. METHODS: Cells were treated with triptolide and viability and caspase-3 activity were measured using colorimetric assays. Annexin V, propidium iodide and acridine orange staining were measured by flow cytometry. Immunofluorescence was used to monitor the localization of cytochrome c and LC3 proteins. Caspase-3, Atg5 and Beclin1 levels were downregulated by exposing cells to their respective siRNA. RESULTS: We show that triptolide induces apoptosis in MiaPaCa-2, Capan-1 and BxPC-3 cells and autophagy in S2-013, S2-VP10 and Hs766T cells. Triptolide-induced autophagy has a pro-death effect, requires autophagy-specific genes, atg5 or beclin1, and is associated with the inactivation of the Akt/mTOR/p70S6K pathway and the upregulation of the ERK1/2 pathway. Inhibition of autophagy in S2-013 and S2-VP10 cells results in cell death via the apoptotic pathway whereas inhibition of both autophagy and apoptosis rescues cell death. CONCLUSIONS: This study shows, for the first time, that triptolide kills pancreatic cancer cells by two different pathways. It induces caspase-dependent apoptotic death in MiaPaCa-2, Capan-1 and BxPC-3 and caspase-independent autophagic death in metastatic cell lines, S2-013, S2-VP10 and Hs766T, thereby making it an attractive chemotherapeutic agent against a broad spectrum of pancreatic cancers.